A Linguistic Analysis of Lexical and Structural Ambiguity in Christopher Nolan's Oppenheimer - Ari Arfian; Sayyid Khairunas; Ary Iswanto Wibowo; Retno Rahayuningsih; Rizky Mirani (Journal of Applied Linguistics, 2026)
This study aims to analyze how Oppenheimer employs ambiguity as a storytelling device to enrich the narrative and encourage audiences to critically interpret the ideas and messages conveyed in the film. A descriptive qualitative method was employed to examine lexical and structural ambiguities found in the dialogues spoken by the main character, J. Robert Oppenheimer, portrayed by Cillian Murphy. The findings reveal a total of 24 ambiguous dialogues, consisting of 17 instances of lexical ambiguity and 7 instances of structural ambiguity. Lexical ambiguity occurs when a word has more than one possible meaning, potentially leading to different interpretations. Structural ambiguity arises from sentence structures that allow multiple interpretations due to their grammatical arrangement. These findings suggest that ambiguity plays a significant role in shaping the film’s narrative by encouraging viewers to interpret the dialogues from different perspectives. Rather than creating confusion, the use of ambiguity enhances the complexity of the characters, supports the thematic depth of the story, and promotes critical engagement with the film’s underlying messages. Keywords : Linguistics, Semantics, Lexical, Structural, Ambiguity